Penggunaan Larutan Biji Buah Pinang (Areca catechu L.) terhadap Lama Penyimpanan dan Kualitas Telur Bebek (Marginae sp.) - Dharmawibawa, Iwan Doddy (Biocaster : Jurnal Kajian Biologi, 2022)
Eggs as a staple food for the community are increasingly in demand because they are very easy to obtain, easy to process and have high protein content. Duck eggs stored at room temperature can only last 10-14 days, after which the eggs have decreased in quality. The purpose of this study was to determine the effect of using betel nut seed solution as a preservative on the storage time and quality of duck eggs. This type of research is a True-experimental study with a Completely Randomized Design (CRD), two factorial, consisting of concentration treatments (0%, 15%, 30%, 45%, and 60%) and storage time treatments (14 days, 21 days, and 28 days) with 3 replicates. Chemical and physical test data were analyzed using the ANOVA test (5%) using SPSS for Windows version 20.0. The interaction of betel nut seed solution concentration and storage time gave no significant effect on the pH value (Fhit = 1.125 < Ftab = 1.375), Yolk Index (Fhit = 1.002 < Ftab = 1.454), and Weight Loss (Fhit = 0.614 < Ftab = 0.638). However, the length of storage of duck eggs had a significant effect on the yolk index (Fhit = 21.821 > Ftab = 21) and weight loss (Fhit = 12,569 > Ftab = 12.001).